2021
DOI: 10.3390/foods10051069
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of COVID-19 Impact on the Food and Beverages Industry: China and India Perspective

Abstract: The sudden breakout of coronavirus disease (COVID-19) rapidly spread across the globe, leaving no country behind in being affected by the global pandemic in the year 2019–20. As COVID-19 commenced, within months two major Asian giants initiated the norms of social distancing and lockdowns in their societies. The indiscriminate nature of the current pandemic has not only impacted the health and quality of life of people but has also disrupted the global economy, supply chains, and countries all over the world. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 73 publications
0
39
1
2
Order By: Relevance
“…Examining the relation between BCT and various industries may aid in understanding the significance of these technologies, particularly in light of the COVID-19 outbreak. According to our findings, the food and agricultural sector has the most commonly utilized BCT, with 19 articles addressing COVID-19 conditions [5,56,57,66,71,79,82,83,85,87,89,94,100,101,103,106,109,110,114]. With 12 research papers since the outbreak, the healthcare industry has made a significant contribution to the reviewed articles.…”
Section: Industry Sectorsmentioning
confidence: 86%
See 3 more Smart Citations
“…Examining the relation between BCT and various industries may aid in understanding the significance of these technologies, particularly in light of the COVID-19 outbreak. According to our findings, the food and agricultural sector has the most commonly utilized BCT, with 19 articles addressing COVID-19 conditions [5,56,57,66,71,79,82,83,85,87,89,94,100,101,103,106,109,110,114]. With 12 research papers since the outbreak, the healthcare industry has made a significant contribution to the reviewed articles.…”
Section: Industry Sectorsmentioning
confidence: 86%
“…Table 2 The findings indicate that, of all the BCT categories, digitalization had the highest frequency in the reviewed studies, with 22 articles out of 72 [3,13,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. With ten articles, visibility was also one of the most common BCT [5,20,[77][78][79][80][81][82][83][84]. Sixteen of the papers looked at the impact of both digitization and visibility on the SC and the COVID-19 pandemic simultaneously [5,23,[85][86][87][88][89][90][91][92][93][94][95][96][97][98].…”
Section: Blockchain Technologiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Some data from the past global economic crisis have shown that lower purchasing power of consumers causes only minimal changes in the consumption of food and beverage items. In the case of food and beverages products, it was found that the demand for packaging materials grew during the COVID-19 crisis, because the final consumption of these products mainly took place in households [17][18][19]. Changes in consumer behavior, caused by the lockdowns in several countries around the world in 2020, will be reflected during the years 2021 and 2022, because in these years the consumption of beverage cans will be evident.…”
Section: Introductionmentioning
confidence: 99%